2019
DOI: 10.1111/jce.14248
|View full text |Cite
|
Sign up to set email alerts
|

The desire for physiological pacing: Are we there yet?

Abstract: Pacing is a well established therapy for bradycardia support and certain types of heart failure. Despite technological advances the optimal pacing lead position remains controversial. Right ventricular pacing, particularly apical has been the site of choice but the induction of abnormal cardiac depolarization and the recognition of an increased risk of impairment of left ventricular systolic function, heart failure and mortality has driven a desire for a true physiological pacing system. A number of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 124 publications
(320 reference statements)
0
7
0
2
Order By: Relevance
“…Also, the simplistic approach used in the current study and previous studies, dividing the RV lead position into arbitrary segments without consideration of individual electroanatomical differences may have limited clinical relevance. Perhaps, the search for an optimal RV lead implantation site needs to move towards physiological pacing including His bundle pacing and left bundle branch pacing [ 21 ]. However, widespread use of such methods could have long prospects and may not be relevant for all patients in need of a pacemaker.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the simplistic approach used in the current study and previous studies, dividing the RV lead position into arbitrary segments without consideration of individual electroanatomical differences may have limited clinical relevance. Perhaps, the search for an optimal RV lead implantation site needs to move towards physiological pacing including His bundle pacing and left bundle branch pacing [ 21 ]. However, widespread use of such methods could have long prospects and may not be relevant for all patients in need of a pacemaker.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa maneira, a busca por uma forma de estimulação artificial que mantenha o sincronismo intra e interventricular, além da correção da bradiarritmia, é uma necessidade de relevância clínica que vem sendo remetida à chamada estimulação fisiológica. 122,123 A estimulação direta do sistema de condução é a maneira mais fisiológica de estimulação ventricular artificial porque mantém a ativação elétrica natural do coração, uma vez que o estímulo segue pelas vias normais de condução especializada (His-Purkinje), evitando a dissincronia induzida pela estimulação muscular do VD. 124 Sharma et al demonstraram, em estudo não randomizado com 202 pacientes em seguimento de 2 anos, que a estimulação pelo feixe de His foi superior à estimulação convencional pela ponta do VD.…”
Section: Estimulação Direta Do Sistema Excito-condutor Cardíaco (Feix...unclassified
“…Dessa maneira, a busca por uma forma de estimulação artificial que mantenha o sincronismo intra e interventricular, além da correção da bradiarritmia, é uma necessidade de relevância clínica que vem sendo remetida à chamada estimulação fisiológica. 122 , 123 …”
Section: 11 Estimulação Direta Do Sistema Excito-condutor Cardíaco (F...unclassified
“…66 Importantly, there is no present role for BiV in patients with normal LVEF and wide QRS or bradyarrhythmia, as studies have shown no difference in symptoms or quality of life despite a greater risk of implant-related complications. 67,68 While the majority of BiV pacing is indicated for the outpatient heart failure setting, an interesting and developing field is the use of physiologic BiV pacing to "rescue" a patient in the intensive care setting when it appears vasopressors or mechanical support cannot be weaned. There have now been multiple cases showing that this hemodynamic benefit can be significant enough to liberate patients tethered to vasopressors, inotropes, or even ECMO and achieve stability enough to leave the intensive care unit (Table 5).…”
Section: Biventricular Pacingmentioning
confidence: 99%
“…66 Importantly, there is no present role for BiV in patients with normal LVEF and wide QRS or bradyarrhythmia, as studies have shown no difference in symptoms or quality of life despite a greater risk of implant-related complications. 67,68…”
Section: Physiologic Pacing For Hemodynamic Improvementmentioning
confidence: 99%